FTA's proposals integrated in the newly endorsed Voluntary Guidelines on Food Systems and Nutrition of the United Nations Committee on World Food Security (CFS) - CGIAR Research Program on Forests, Trees and Agroforestry (2020)
The Committee on World Food Security (CFS) has endorsed the first-ever Voluntary Guidelines on Food Systems and Nutrition (VGFSyN) which aim to support countries to eradicate hunger and malnutrition in all its forms by utilizing a food systems approach. FTA had an active role in the multi-stakeholder process that led to the approval of the guidelines.